Economies of scale in academic libraries of the University of the Philippines Diliman - Cataylo, Neville C (2005)
This study examines scale economies in the U.P. Diliman academic libraries using two-year cross-section pooled data on 26 libraries. The data was fitted into a cost function under a natural log linear model. Two collection outputs, nine service outputs and a dummy variable were included in the cost function. The choice of variables was intended to reflect library operations. The study finds that significant economies of scale exist in the U.P. Diliman libraries with the sum of regression coefficients being equal to 0.64. The regression model explains 80.4 percent of the variation of total cost. The results show that that volumes held and circulation to be very important aspects of the U.P. library network and essential measures of library performance. The results also show a fairly strong association between total cost and the usage of Filipiniana materials, periodicals, audiovisuals and group presentations. The serials collection, as measured by the number of serial titles, the use of reserve materials, newspapers and the provision of reference services are not found to be significant contributors to the cost of U.P. Diliman libraries.